Analysis of Short-Term Results after Introduction of Robotic Gastrectomy for Gastric Cancer at Our Hospital - Kawada, Junji; Maruyama, Minami; Nomura, Tomonori; Mizuno, Manatsu; Fukada, Akio; Kidogami, Shinya; Taniguchi, Yoshiki; Asukai, Kei; Osawa, Hideki; Mokutani, Yukako; Kishimoto, Tomoya; Hirose, Hajime; et al. (Gan to kagaku ryoho, 2024)
Robotic gastrectomy(RG)for gastric cancer(GC)has been covered by health insurance since 2018. In this study, we examined the results of RG for GC at our hospital during the initial period of its introduction. From August 2022 to May 2023, we retrospectively examined the surgical outcomes and short-term postoperative outcomes of the first 9 patients who underwent RG for GC at our hospital. The median patient age was 77(67-82) years, gender was 4 males and 5 females, and distal gastrectomy was performed in all patients. The median operative time was 410(323-486)min, blood loss was 5(1-140)mL, postoperative hospital stay was less than 9 days in all patients, and there was no conversion to laparoscopic or open surgery. There were no postoperative complications of Clavien-Dindo Grade Ⅱ or above. In this study, RG for GC was performed safely without intraoperative or postoperative complications.